Seaters Preference as a Component of Servicescape in Hotel Industry Semarang - Kholifatunnisa, Aisyah -; Riyadi, Riyadi -; Nahar, M - (Politeknik Negeri Semarang, 2021)
The purpose of this research was to determine the ideal seater combination for hotels industry based on customer preference at Semarang City. The samples of this research were 100 respondent selected by implementing incidental sampling technique. Primary data was collected by distributing questionnaires while secondary data was obtained from literature study. This research used a conjoint analysis with the rank based technique. The result indicated that the most ideal seater combination was wood – fabric – cushion. The highest level of the attribute relative importance was cover with a weight of 0.483. Hotel industry in Semarang was recommended to use seater with wood – fabric – cushion combination and suggested the use of cover on the seater